John H. Oakley (ed.). Athenian Potters and Painters - Osborne, Robin (Journal of Greek Archaeology, 2017)
This volume, dedicated to Alan Shapiro, follows the format of the two previous volumes of Athenian Potters and Painters (and, as in volume 2, with 32 splendid pages of colour plates). This is unfortunate. The papers appear in alphabetical order of their author, regardless of chronology or subject-matter, with no attempt to shape the book to make papers that talk to each other appear next to each other. Bibliographical references are buried in the notes at the end of each chapter, with no consolidated bibliography. Most extraordinary of all, there is no index. For those professionally interested in Greek painted pottery (the volume does not in fact limit itself to Athenian potters and painters and shows rather minimal interest in potters), it is no doubt convenient to have these papers between a single set of hard covers, but for any Greek archaeologist or historian who wants to know whether there is anything here for her, there is no way of telling. They would have a better chance of finding what is interesting here if these papers had been in a journal whose text could be searched online.